Prevalence of Lingual eruption of mandibular permanent incisors and relationship between lingual eruption and arch- form in 6-8 years old Children in kerman - R Shojaeipour; Sh Arya (Isfahan University of Medical Sciences, 2009)
Introduction: The eruption of mandibular permanent incisors lingual to retained primary incisorsis often a source of concern for parents. It is seen both in patients with an obvious arch lengthinadequacy and in those with a desirable amount of spacing of the primary incisors. Because nostatistics on prevalence of lingual eruption of mandibular permanent incisors exists, the aim of thepresent study was to investigate the prevalence of lingual eruption of mandibular permanentincisors and relationship between lingual eruption an arch- form in 6-8 years old children inkerman during autumn 2006.Material and Methods: In this descriptive-cross sectional study, 4278 students (%50 girl, 50%boy) were selected randomly form 50 Schools in Kerman. Data including age, sex, position oflingual eruption of mandibular permanent incisors and dental arch form were recorded and thenanalyzed using t and chi- square tests.Results: The prevalence of Lingual eruption of mandibular permanent incisors was 2.2%. Lingualeruption of mandibular permanent incisors in girls was significantly more than boys (p value